Rapid densification of forsterite ceramic via microwave sintering - Meng T.Y.; Yong T.C.; Singh R.; Ching T.Y.; Kar Y.B. (Trans Tech Publications Ltd, 2023)
Bioceramics; Ceramic materials; Microwave heating; Microwaves; Olivine; Solid state reactions; Conventional sintering; Forsterite ceramics; Forsterites; Lower sintering temperatures; Microstructure evaluations; Microwave sintering; Rapid densification; Solid state reaction method; Sintering